The Central Bright Spot Sign: A Potential New MR Imaging Sign for the Early Diagnosis of Anterior Ischemic Optic Neuropathy due to Giant Cell Arteritis - Remond, P.; Attyé, A.; Lecler, A.; Lamalle, L.; Boudiaf, N.; Aptel, F.; Krainik, A.; Chiquet, C. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: A rapid identification of the etiology of anterior ischemic optic neuropathy is crucial because it determines therapeutic management. Our aim was to assess MR imaging to study the optic nerve head in patients referred with anterior ischemic optic neuropathy, due to either giant cell arteritis or the nonarteritic form of the disease, compared with healthy subjects.MATERIALS AND METHODS: Fifteen patients with giant cell arteritis–related anterior ischemic optic neuropathy and 15 patients with nonarteritic anterior ischemic optic neuropathy from 2 medical centers were prospectively included in our study between August 2015 and May 2016. Fifteen healthy subjects and patients had undergone contrast-enhanced, flow-compensated, 3D T1-weighted MR imaging. The bright spot sign was defined as optic nerve head enhancement with a 3-grade ranking system. Two radiologists and 1 ophthalmologist independently performed blinded evaluations of MR imaging sequences with this scale. Statistical analysis included interobserver agreement.RESULTS: MR imaging scores were significantly higher in patients with giant cell arteritis–related anterior ischemic optic neuropathy than in patients with nonarteritic anterior ischemic optic neuropathy (P <= .05). All patients with giant cell arteritis–related anterior ischemic optic neuropathy (15/15) and 7/15 patients with nonarteritic anterior ischemic optic neuropathy presented with the bright spot sign. No healthy subjects exhibited enhancement of the anterior part of the optic nerve. There was a significant relationship between the side of the bright spot and the side of the anterior ischemic optic neuropathy (P <= .001). Interreader agreement was good for observers (κ = 0.815).CONCLUSIONS: Here, we provide evidence of a new MR imaging sign that identifies the acute stage of giant cell arteritis–related anterior ischemic optic neuropathy; patients without this central bright spot sign always had a nonarteritic pathophysiology and therefore did not require emergency corticosteroid therapy.AIONanterior ischemic optic neuropathyFFEfast-field echoGCAgiant cell arteritisGCA-AIONgiant cell arteritis–related anterior ischemic optic neuropathyNA-AIONnonarteritic anterior ischemic optic neuropathy